Immigration Policy and Foreign Population in Switzerland - Gross, Dominique M. (World Bank, Washington, DC, 2012)
With more than 20 percent, Switzerland is one of the countries with the largest foreign population. Since 1970 the government has tried to manage the flows of migrants in the hope of reconciling a chronic excess demand for labor with mounting pressures from nationalistic groups to control the level of foreign population. A policy of quotas on work permits has been effective in controlling the entry of new workers. Nevertheless, the overall dynamic of the system has led to an ever-increasing share of newcomers not covered by quotas. Because of institutional and economic changes, the outflow did not react to economic incentives as the government expected. Hence, at the beginning of the 21st century, the link between the instruments of immigration policy and its goal has become very weak and the level of foreign population is at an all time high. However, a new era has begun with an agreement on free mobility with European Union and European Free Trade Area (EFTA) countries.